Factors Affecting Purchasing Behavior of Environmental-friendly Products among Thai and Laos Consumers in Loei Province - มีทรัพย์ทอง, จารุพร (Business Administration and Management Journal Review, 2018)
This research aimed at studying personal characteristics affecting purchasing behavior of environmental-friendly products among Thai and Laos consumers in Loei province, and exploring relationship between needs in purchasing environmental-friendly products in terms of product, price, distribution channel and promotion with purchasing behavior of environmental-friendly products among Thai and Laos consumers in Loei province. This quantitative research employed 390 Thai and Laos consumers, 229 Thais and 161 Laos, in Loei province as a sample group by accidental sampling technique using bilingual questionnaires with 6 factors: (1) personal characteristics (2) needs of products (3) needs of price (4) needs of distribution channel (5) needs of marketing promotion and (6) purchasing behavior of environmental-friendly products. Descriptive statistics, T-test, F-test, LSD’s comparison, Pearson’s correlation and multiple regression were adopted for data analysis. The research revealed 1) Thai and Laos consumers with different ages, incomes and careers had different purchasing behavior of environmental-friendly products significantly at 0.05 statistical level; 2) needs of products, price, distribution channel and marketing promotion had relationship with purchasing behavior of environmental-friendly products; and 3) factors of needs of product, distribution channel and marketing promotion had influence towards purchasing behavior of environmental-friendly products.